2022
DOI: 10.1111/ajt.17140
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 therapeutics and outcomes among solid organ transplant recipients during the Omicron BA.1 era

Abstract: Treatment outcomes associated with the use of novel COVID‐19 therapeutics in solid organ transplant recipients (SOTR) are not well described in the literature. The objective of this analysis was to characterize 30‐day hospitalization and other key secondary endpoints experienced by outpatient SOTR with mild–moderate COVID‐19 treated with nirmatrelvir/ritonavir (NR), sotrovimab, or no SARS‐CoV‐2 specific treatment. This IRB‐approved, retrospective study included 154 SOTR with a documented positive SARS‐CoV‐2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 21 publications
3
65
0
Order By: Relevance
“…Figure 1 shows the flow diagram of study selection according to its title, abstract, and full text. After removing duplicated records, seventeen studies, 19 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 (two RCTs and fifteen observational studies) with 27,429 patients were included in the meta‐analysis. The main characteristics of included studies are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the flow diagram of study selection according to its title, abstract, and full text. After removing duplicated records, seventeen studies, 19 , 20 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 (two RCTs and fifteen observational studies) with 27,429 patients were included in the meta‐analysis. The main characteristics of included studies are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Data are available online for the included studies. 19,20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we assume that more stringent outpatient management of the LTR with breakthrough infections might have prevented the development of AKI and bacterial superinfections leading to hospitalizations in several cases, as would have the early initiation of antiviral treatment. In several published studies, the use of antiviral and early antibody treatment which showed excellent tolerability significantly reduced mortality, and the need for supplemental oxygen in SOT [ 39 , 40 , 41 , 42 , 43 , 44 ]. Therefore, early administration of antiviral treatment should be considered in LTR with comorbidities and a higher age who are thus at an increased risk for a severe disease course.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study evaluated nirmatrelvir/ritonavir, sotrovimab and no SARS-CoV-2 specific treatment (92). The results are similar and claim for the use of SARS-CoV-2 specific agents in the treatment of SOT recipients with COVID-19 infection.…”
Section: Direct-acting Small Molecule Sars-cov-2 Antiviralsmentioning
confidence: 59%